Penerapan Teknologi Ternak Lele di Desa Patapan Kecamatan Torjun Kabupaten Sampang Madura - Wiwin Retnowati; M. Gandul Atik Yuliani; Bambang Sumaryono (Jurnal ABM Mengabdi, 2017)
The purpose of KKN PPM (Kuliah Kerja Nyata Pembelajaran Pemberdayaan Masyarakat, Student Community Service Community Empowerment Learning) program is to overcome the problems encountered in the village of Patapan, which was the low income of the residents. The solution to solve the problem is to empower the villagers through the program of utilizing yard land with appropriate technology through training and assistance of catfish farming. The implementation of KKN PPM activities in Patapan Village, Subdistrict Torjun, Disctrict Sampang, Madura was succesful. The enthusiasm of the people of Patapan Tengah and Jergut sub-villages in participating in this activity was quite high. The outcome seen in the community after counseling and mentoring on knowledge, understanding and skills of appropriate technology of catfish farming was the formation of 6 groups of catfish farmers in sub- village Patapan Tengah and 1 group of catfish farmers in sub-village Jergut.